Solid‐Supported Catalysts for Organic Functional Group Transformations. Issue 4 (8th March 2023) - Adeyeye Nafiu, Sodiq; Ajeebi, Afnan M.; Alghamdi, Huda S.; Aziz, Md. Abdul; Nasiruzzaman Shaikh, M.
Abstract: Design of solid‐supported metal catalysts (SSMCs) has made an increasingly important contribution to heterogeneous catalysis in terms of fundamental understanding and technological applications. For instance, industrial use of supported catalysts for oxidation, reduction, and C−C bond formation reactions is highly prevalent. The reason behind this is that such catalysts are economical, have high thermal stability, dispersion, high exposed surface area, and above all, high reusability (up to multiple subsequent cycles). Such characteristics make supported catalysts ideal for green synthesis. However, unlike homogeneous catalysis, heterogeneous catalysis is widely applied in crude oil refining, the pharmaceutical industry, water purification, natural product synthesis, and environmental catalysis. Carbon‐carbon bond formation reactions are frequently used in the organic synthesis using SSMCs. SSMCs are attractive to synthetic chemists due to their easy recovery and excellent stability compared to unsupported metal catalysts. However, the major drawback of SSMCs is related to metal sintering at elevated temperatures caused by weak interactions between the metal and solid support in SSMCs. This review highlights major advancements in SSMCs. Three commonly reported solid supports for metal catalysts, such metal oxides, carbonaceous materials, and polymeric compounds, are discussed. Moreover, a series of thermo‐ and photocatalyzed reactions, such as hydrogenation, carbon‐carbon bond formation, oxidation reactions and multicomponent reactions and the effect of variable supports towards activity and selectivity are demonstrated. Abstract : This review highlights major advancements in solid‐supported metal catalysts. A series of reactions, such as hydrogenation, carbon‐carbon bond formation, and oxidation reactions, and the effect of variable supports towards activity and selectivity are demonstrated.